Exo-miR-144-3p as a promising diagnostic biomarker for depressive symptoms in heart failure - Ruting Wang; Kai Huang; Yuehua Feng; Jiahao Duan; Hangfeng Ying; Qianyuan Shi; Yi Zhang; Riyue Jiang; Ling Yang (Neurobiology of Disease, 2024)
Abstracts: Aims: The prevalence of depression is higher in heart failure (HF) patients. Early screening of depressive symptoms in HF patients and timely intervention can help to improve patients' quality of life and prognosis. This study aims to explore diagnostic biomarkers by examining the expression profile of serum exosomal miRNAs in HF patients with depressive symptoms. Methods: Serum exosomal RNA was isolated and extracted from 6 HF patients with depressive symptoms (HF-DS) and 6 HF patients without depressive symptoms (HF-NDS). High-throughput sequencing was performed to obtain miRNA expression profiles and target genes were predicted for the screened differentially expressed miRNAs. Biological functions of the target genes were analyzed through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Subsequently, we collected serum exosomal RNAs from HF-DS (n = 20) and HF-NDS (n = 20). The differentially expressed miRNAs selected from the sequencing results were validated using reverse transcription quantitative polymerase chain reaction (RT-qPCR). Finally, the diagnostic efficacy of the differentially expressed exosomal miRNAs for HF-DS was evaluated by using receiver operating characteristic (ROC) curves. Results: A total of 19 significantly differentially expressed exosomal miRNAs were screened by high-throughput sequencing, consisting of 12 up-regulated and 7 down-regulated exosomal miRNAs. RT-qPCR validation demonstrated that the expression level of exo-miR-144-3p was significantly down-regulated in the HF-DS group, and the expression levels of exo-miR-625-3p and exo-miR-7856-5p were significantly up-regulated. In addition, the expression level of exo-miR-144-3p was negatively correlated with the severity of depressive symptoms in HF patients, and that the area under the curve (AUC) of exo-miR-144-3p for diagnosing HF-DS was 0.763. Conclusions: In this study, we examined the serum exosomal miRNA expression profiles of HF patients with depressive symptoms and found that lower level of exo-miR-144-3p was associated with more severe depressive symptoms. Exo-miR-144-3p is a potential biomarker for the diagnosis of HF-DS.